Boronic ester-based vitrimeric methylvinyl silicone elastomer with "solid-liquid" feature and rate-dependent mechanical performance. (16th January 2023) - Zhao, Yongsheng; Qin, Tian; Jiang, Chaobo; Li, Jialiang; Xiong, Youhao; Liu, Shiyuan; Qin, Jianbin; Shi, Xuetao; Zhang, Guangcheng
Abstract: Vitrimer chemistry can integrate reprocessability, recyclability, self-healing and good creep-resistance into polymers through covalent adaptive network structure. In particular, reactive processing shows great potential to convert commercial polymers into vitrimers in industrial scale. In this work, vitrimeric silicone elastomer was successfully prepared in a one-step peroxide-induced thiol-ene click reaction between thiol-terminated boronic ester and vinyl groups of commercial methylvinyl silicone rubber (MVQ) via reactive processing. It was found that MVQ vitrimer elastomer shows good reprocessability, self-healing property, excellent elasticity and a similar gel content to that of traditional peroxide-crosslinked MVQ rubbers. Based on classical Arrhenius theory, the calculated activation energy ( E a ) of B–O dynamic bond in MVQ vitrimer is 28.5 kJ/mol along with a topology-freezing transition temperature ( T v ) of 6.4 °C. Intriguingly, the fabricated MVQ vitrimer shows a strongly rate-dependent mechanical response, i.e., larger mechanical strength at higher deformation rate, which is mainly due to fast bond-exchange rate of the B–O bonds even at room temperature. MVQ vitrimer shows a "solid-liquid" feature, that is, exhibiting liquid-like behavior at longer obeservation time or when stretched at low strain rate while acting as solid elastomer at high strain rate. Notably, the tensile toughness (@500% strain) can obtain nearly 1.6-fold increase to 47.59 MJ/m 3 from 18.58 MJ/m 3 when increasing tensile speed, indicating an excellent energy-dissipative behavior especially at high deformation rate. Therefore, our work can provide guidance for molecular design and reactive processing of high-performance vitrimeric silicone elastomers toward industrial applications. Graphical abstract: Image 1 Highlights: Commerical methyvinyl silicone rubber(MVQ) was transformed into MVQ vitrimer elastomer through the combination of thiol-ene chemistry and reactive processing. The prepared MVQ vitrimer elastomer has good reprocessability, self-healing property and rate-dependent mechanical performance. MVQ vitrimer elastomer has an estimated activation energy( E a ) of 28.5 kJ/mol and a topological freezing temperature( T v ) of 6.4 °C.